Neuroeconomics, naturalism and language - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2008)
Neuroeconomics stays in the center of the ongoing naturalistic turn in economics. It portrays the individual as a complex system of decision making mechanisms and modules. This results into a conceptual tension with the standard economic notion of the unity of the actor that is a systemic property of economic coordination. I propose to supplement neuroeconomics with a naturalistic theory of social coordination. Recent neurobiological and psychological research strongly supports claims made by some heterodox economists that the identity of actors emerges from social interaction, especially in the context of the use of language. Therefore, I argue that the completion of the neuroeconomic paradigm requires a naturalistic theory of language. I provide some sketches based on teleosemantics and memetics, and exemplify the argument by a naturalist account of money.
urn:nbn:de:101:1-2008121084
Keywords: A12; B41; D87; 330; Naturalism; neuroeconomics; individual identity; language and economics; naturalistic theory of social interaction